(untitled) - Miller, Mark (Hoboken, N.J., 2004)
A comprehensive reference that addresses the need for solid understanding of the operation of IP networks, plus optimization and management techniques to keep those networks running at peak performance. Uniquely distinguished from other books on IP networks, as it focuses on operation and management support, and is not just another treatise on protocol theory. Includes many practical case studies as further illustration of the concepts discussed.
Keywords: Computer networks,TCP/IP (Computer network protocol),Network performance (Telecommunication),Internet,Mạng máy tính; Management,Quản trị